A Simple, Rapid, and Efficient Method for Isolating Mesenchymal Stem Cells from the Entire Umbilical Cord. Issue 7 (July 2016) - Dehkordi, Mehdi Banitalebi; Madjd, Zahra; Chaleshtori, Morteza Hashemzadeh; Meshkani, Reza; Nikfarjam, Laleh; Kajbafzadeh, Abdol-Mohammad
Several reports have been published on the isolation, culture, and identification of mesenchymal stem cells (MSCs) from different anatomical regions of the umbilical cord (UC). UC is suitable for standardizing methods of MSC isolation because it is a uniform source with high MSC numbers. Although the UC is considered a medical waste after childbirth, ethical issues for its use must be considered. An increased demand for MSCs in regenerative medicine has made scientists prioritize the development of MSC isolation methods. Several research groups are attempting to provide a large number of high-quality MSCs. In this study, we present a modulated explant/enzyme method (MEEM) to isolate the maximum number of MSCs from the entire UC. This method was established for the isolation of MSCs from different anatomical regions of the UC altogether. We could retrieve 6 to 10 million MSCs during 8 to 10 days of primary culture. After three passages, we could obtain 8–10 × 10 8 cells in 28–30 days. MSCs isolated by this method express CD73, CD90, CD105, and CD44, but they do not express hematopoietic markers CD34 and CD45 or the endothelial marker CD31. The genes SOX2, OCT4, and NANOG are expressed in isolated MSCs. The capacity of these MSCs to differentiate into adipocytes and osteocytes highlights their application in regenerative medicine. This method is simple, reproducible, and cost efficient. Moreover, this method is suitable for the production of a large number of high-quality MSCs from an UC in less than a month, to be used for cell therapy in an 80-kg person.